(untitled) (Research, Society and Development, 2020)
In the school context, Science Education is an existing discipline to instill students’ knowledge, mobilizing in them a critical and investigative spirit. Starting from cognitive knowledge to reality, the learner will incorporate concepts that, through application in problem situations, will be mediated by the relationships in which he finds himself. It was observed that this form of pedagogical work can contribute to the production of situations favorable to the pursuit of knowledge in the school space. In this study we aim to understand the perception of teachers about Science Teaching during the evaluation processes. This research has a qualitative approach. The methodology includes instructions regarding subjects, inquisitions, groupings and weightings of information. The results of the research show how to delimit: absence of a certain connection between Science Teaching and assessment with students’ lives; inexistence of any advice and didactic basis and are able to make the results viable; certain elaboration guided with the goal of enabling students to an evaluative practice. As viability: Science Teaching within an evaluation framework can provide components about peculiarities of education in public schools; this conduct appreciates the role of the master and organizational. They lead to referrals about Science Teaching and its evaluative execution since it is essential to consider the link between Science Teaching and the existence of students, schools and educators.